Trends in risk factor control in patients with gout: data from the National Health and Nutrition Examination Survey, 2007–2018. (26th April 2022) - Li, Likang; Tian, Junzhang; Wang, Ruoting; Adachi, Jonathan D; Chen, Bo; Qu, Hongying; Li, Guowei
Abstract: Objectives: To explore trends in risk factor control (hypertension, diabetes mellitus, hyperlipidaemia) in patients with gout and medication use among those whose risk factor control targets were not achieved. Methods: We used the data from National Health and Nutrition Examination Survey (NHANES) between 2007–2008 and 2017–2018 for analyses. The study samples were weighted so that they could be representative of the non-institutionalized US population. We conducted a cross-sectional analysis to assess trends in risk factor control and medication use, and employed logistic regression analyses to explore patient characteristics associated with risk factor control. Results: The prevalence of participants in whom blood pressure control target was achieved decreased from 64.6% in 2007–2008 to 55.3% in 2017–2018 ( P -value for trend = 0.03). The percentage of participants whose glycaemic, lipid or all three risk factor control targets were achieved remained stable temporally ( P > 0.05). Some patient characteristics were significantly related to risk factor control, including age 45–64, age ≥65, Asian Americans, non-Hispanic Blacks, higher family income, and being overweight and obese. A trend towards increased use of glucose-lowering medication was found (from 71.0% in 2007–2008 to 94.7% in 2017–2018, P < 0.01), while the prevalence of taking blood pressure-lowering and lipid-lowering medications remained stable ( P > 0.05). Conclusion: Based on NHANES data, a significant trend towards decreased blood pressure control was observed in patients with gout, while glycaemic and lipid control levelled off. These findings emphasize that more endeavours are needed to improve management of cardiovascular risk factors in patients with gout.